2010
DOI: 10.1002/fuce.200900135
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Accurate Method for High‐Temperature PEM Fuel Cell Characterisation

Abstract: A set of basic parameters for any polymer electrolyte membrane fuel cell (PEMFC) includes the Tafel slope b and the exchange current density j* of the cathode catalyst, the oxygen diffusion coefficient Db in the cathode gas‐diffusion layer and the cell resistivity Rcell. Based on the analytical model of a PEMFC [A. A. Kulikovsky, Electrochim. Acta (2004) 617], we propose a two‐step procedure allowing to evaluate these parameters for a high‐temperature PEMFC. The procedure requires two polarisation curves measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The effective diffusion coefficient is corrected accounting for the porosity and the tortuosity of the GDL [4]. The resulting effective diffusion coefficient of oxygen is in the order of 0.03 cm 2 s -1 , similar to that reported in [25] where a value of 0.02 cm 2 s -1 is reported. The low value of the diffusion coefficient may be due to the presence of a microporous layer (MPL): a typical overall diffusion coefficient of GDL with MPL is in the range of 0.03 cm 2 s -1 [26].…”
Section: Through Mea Subdomain In Steady Statesupporting
confidence: 74%
See 1 more Smart Citation
“…The effective diffusion coefficient is corrected accounting for the porosity and the tortuosity of the GDL [4]. The resulting effective diffusion coefficient of oxygen is in the order of 0.03 cm 2 s -1 , similar to that reported in [25] where a value of 0.02 cm 2 s -1 is reported. The low value of the diffusion coefficient may be due to the presence of a microporous layer (MPL): a typical overall diffusion coefficient of GDL with MPL is in the range of 0.03 cm 2 s -1 [26].…”
Section: Through Mea Subdomain In Steady Statesupporting
confidence: 74%
“…Since EIS is a measurement of the slope of the losses, no effect is observed. [14]; 6 10 -2 [15] a σ (-) 2 2.6 10 -2 [35] a C (-) 0.85 0.8 [39]; 0.78 [25]; 0.89 [20]; 1 [42]; 0.73 [35]; 1 [14]; 0.8 [15] b (mV dec -1 ) 101 108 [39]; 111 [25]; 91 104 [21]; 97 [20]; 86 [42]; 118 [35]; 86 [14]; 108 [15] i* (A cm -3 ) 1.55 10 -2 1.3 10 -3 [14] i* (A cm -2 Pt ) 4.7 10 -9 a 1.8/24 10 -9 [21]; 1.4 10 -9 [20]; 29 10 -9 [35] i* δ CL (A cm -2 ) 4.7 10 -5 2.1/4.1 10 -5 [39]; 1.5 10 -5 [25]; 6.9 10 -6 [42]; 3.8 10 -5 [15] D O2 (cm 2 s -1 ) 10.8 10 -4 et À1 el (-) 1.2 10 -2 3.2 10 -2 [29]; 14 10 -2 [14] C DL (F cm -3 ) 9 140 [14] C DL (F cm -2 ) 2 7 10 -3 50 10 -3 [15] s 0 e 1:5 PA (S cm -1 ) 2.79 10 -2 13 10 -2 [20]; 0.16 10 -2 [14] a Exchange current density calculated with an active area of 145 cm 2 cm -2 measured by cyclic voltammetry and O 2 solubility in PBI + phosphoric acid from Ref. [21].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Impregnation with about 20 mg cm À2 of H 3 PO 4 was reported. 68 In our recent paper, 44 we demonstrated that better results can be obtained by impregnating the anode and the cathode with different amounts of H 3 PO 4 , namely 20 mg cm À2 and 8 mg cm À2 , respectively. However, scarce information may be found in the literature on this issue, and further systematic work is needed for MEA optimization.…”
Section: E Mea Assembly Functional Propertiesmentioning
confidence: 94%
“…The ink was spray-coated on the anode and cathode gas diffusion layers (GDL, Sigracet 10DC, SGL Group). Another recipe employing a different binder was proposed by Kulikovsky et al 68 In this case, gas diffusion electrodes (GDEs) with a platinum loading of 1.2 mg cm À2 were prepared by coating an ink containing 20 wt% Pt/C catalyst (HiSPEC 3.000, Johnson Matthey) and PTFE (Dyneon) onto a woven gas diffusion layer (GDL, HT 1400-W, Basf) via an automated doctor blade technique followed by a drying step.…”
Section: E Mea Assembly Functional Propertiesmentioning
confidence: 99%
“…The proton conductivity of the electrolyte membrane and the activity of the catalyst is highly dependent on the temperature. The operating temperature of low‐temperature PEMFCs should be controlled in 60°C to 70°C, while the working temperature of high‐temperature PEMFCs is about 100°C to 200°C . Higher temperatures can increase the rate of electrochemical reaction and diffusion .…”
Section: Introductionmentioning
confidence: 99%